The Effect of Nurses' Anxiety Levels About Covid-19 Transmission on Nurse-to-Patient Caring Behavior In the Inpatient Room - Riya Anita Candra, Vania; Heri Susanti, Indri; Tri Yudono, Danang (Journal of Midwifery and Nursing, 2024)
Nurses' caring behavior is important for patients as service recipients so that it improves the patient's own recovery. Disturbances caused by caregiver anxiety can interfere with caregiver performance. The purpose of this study was to determine the effect of the anxiety level of nursing before the transmission of Covid-19 on nursing behavior in hospital patients. This type of study is a library search with a literature search design. The search strategy to obtain journals used the keywords "Anxiety OR Anxiety AND Covid-19 OR Covid-10 Transmission AND Caring Behavior OR Caring Behavior AND Nurse OR Nurse AND Influence OR The Effect AND Quantitative Study". The results of the literature review revealed that most of the nurses were 30-40 years old, female and had a bachelor's degree in nursing education. Most nurses have anxiety in the category of not anxious, mild anxiety, good caring behavior. Most nurses have good caring behavior. There is an influence on nurses' level of anxiety about Covid-19 transmission on nurses' caring behavior towards patients